MEMETAKAN KONFLIK DI TIMUR TENGAH (TINJAUAN GEOGRAFI POLITIK) - Ruslin, Ismah Tita (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2013)
MiddleEastis aregionwithgeographicalirony. With strong geographicelements and having both physical and non-physical diversepotentials, this region shouldbe politicallypowerful. In fact, Middle East seems like